![image](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B4%7D%28x%2B4%29%7D%7Bx%5E%7B3%7D%28x%2B4%29%7D%20%3D%20%5Cfrac%7Bx%5E%7B4%7D%7D%7Bx%5E%7B3%7D%7D%20%3D%20x%20%3D%20-0.6%3C%2Fp%3E%3Cp%3E%5Cfrac%7Bx%5E%7B4%7D%283x%2B4%29%7D%7Bx%5E%7B2%7D%283x%2B4%29%7D%20%3D%20%5Cfrac%7Bx%5E%7B4%7D%7D%7Bx%5E%7B2%7D%7D%20%3D%20x%5E%7B2%7D%20%3D%20%28-3%5Cfrac%7B2%7D%7B3%7D%29%20%5E%7B2%7D%20%3D%20%28-%5Cfrac%7B8%7D%7B3%7D%29%20%5E%7B2%7D%3D%20%5Cfrac%7B64%7D%7B9%7D%20%3D7%5Cfrac%7B1%7D%7B3%7D)
\frac{x^{4}(3x+4)}{x^{2}(3x+4)} = \frac{x^{4}}{x^{2}} = x^{2} = (-3\frac{2}{3}) ^{2} = (-\frac{8}{3}) ^{2}= \frac{64}{9} =7\frac{1}{3}" alt="\frac{x^{4}(x+4)}{x^{3}(x+4)} = \frac{x^{4}}{x^{3}} = x = -0.6
\frac{x^{4}(3x+4)}{x^{2}(3x+4)} = \frac{x^{4}}{x^{2}} = x^{2} = (-3\frac{2}{3}) ^{2} = (-\frac{8}{3}) ^{2}= \frac{64}{9} =7\frac{1}{3}" align="absmiddle" class="latex-formula">